Basal mass balance and prevalence of ice tongues in the Western ross sea - Gomez-Fell, Rodrigo; Marsh, Oliver J.; Rack, Wolfgang; Wild, Christian T.; Purdie, Heather (Frontiers in Earth Science, 2023)
Ice tongues at the fringes of the Antarctic ice sheet lose mass primarily through both basal melting and calving. They are sensitive to ocean conditions which can weaken the ice both mechanically or through thinning. Ice tongues, which are laterally unconfined, are likely to be particularly sensitive to ocean-induced stresses. Here we examine ice tongues in the Western Ross Sea, by looking into the factors affecting their stability. We calculate the basal mass change of twelve Antarctic ice tongues using a flux gate approach, deriving thickness from ICESat-2 height measurements and ice surface velocities from Sentinel-1 feature-tracking over the same period (October 2018 to December 2021). Basal mass balance ranges between −0.14 ± 0.07 m yr−110 and −1.50 ± 1.2 m yr−1. The average basal mass change for all the ice tongues is (−0.82 ±11 0.68 m of ice yr−1). Low values of basal melt suggest a stable mass balance condition in this region, with low thermal ocean forcing, as other studies have shown. We found a heterogeneous basal melt pattern with no latitudinal gradient and no clear driver in basal melt indicating that local variables are important in the persistence of ice tongues in the absence of a strong oceanographic melting force. Moreover, thanks to the temporal resolution of the data we were able to resolve the seasonal variability of Drygalski and Aviator Ice Tongues, the two largest ice tongues studied.